Building a Culture of Peace for Sustainable Socio-Political and Economic Stability in South Sudan (Journal of Political Science and International Relationship, 2025)
Persistent civil wars, inter-communal clashes, and hostile interpersonal relations have made peace highly elusive in South Sudan; despite numerous local, regional, and international efforts, these instabilities prove resistant to resolution. The endless conflicts have resulted in critical humanitarian crises and social and economic difficulties affecting nearly everyone. The devastating history of violence in the country has entrenched a culture that undermines peace efforts. The article, therefore, explores the root causes of the instabilities, their nature and impact, and advocates for practices such as harmony, reconciliation, the rule of law, and institutional development that foster a Peace culture to break the cycle of violence, ensuring lasting peaceful coexistence and sustainable political and socio-economic stability across the country. Using secondary data from academic articles, and UN reports, the article draws on Émile Arnaud’s pacifism theory, emphasizing nonviolence and peaceful means to achieve peace. Based on the Pacifism theory is the belief that peace is good, that we must work for peace, and that war should be avoided, if not abolished, advocating love, reconciliation, and care as essential values. The article concludes by recommending practices, behaviors, and attitudes that can help various stakeholders develop peace as a lasting cultural norm rather than a temporary fix to achieve enduring stability in South Sudan.